INCREASING THE SALES VALUE OF KEDIRI COFFEE THROUGH THE CREATION OF THE MOUNT WILIS ARABICA DRIP BAG PRODUCT - Mulyaningtiyas, Ratna Dewi; Arisyahidin, Arisyahidin; Askafi, Eka; Luthfiana, Ainul; Septiani, Avita Risky Dwi; Nufus, Farazia Hayatu; Srikalimah, Srikalimah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Indonesia, as one of the world's four coffee suppliers, has the potential to develop coffee cultivation and processing technology, given the still-open market. The slopes of Mount Wilis in Kediri Regency boast 45 hectares of coffee plantations that are still under development and do not yet produce sufficient quantities of coffee. Coffee farmers still live in poverty due to the relatively low selling price and also low production capacity. This community service effort focuses on adding value to Wilis Arabica coffee, creating the Wilis Arabica Drip product. This product can increase its selling price by up to 300% over its original price. roasted beanswithout special packaging. The active involvement of participants (farmer group members) in the training, enabling them to gain hands-on experience rather than simply listening to material, has a positive impact on their motivation to add value to the harvested coffee, turning it into high-value packaged coffee products.